Assessment of demand for and utilization of dental services by insurance coverage in a developing oral health care system - Bayat, Fariborz; Akbarzadeh, Alireza; Monajemi, Farshid (Journal of Dental School, 2019)
Objectives This study aimed to evaluate the relationship between demand for and utilization of dental services by insurance coverage among adults in Iran. Methods A cross-sectional survey based on telephone interviews was done. A total of 6,029 adults participated in this study conducted in Iran. The interviews were carried out using a structured questionnaire and covered dental visits, demographics and socio-economic background. Results Of 6,029 participants, 86% reported having health insurance, 58% had public, and 28% had both public and commercial insurance. Those with both public and commercial insurance coverage had higher odds for dental visits within the past 12 months [odds ratio (OR) = 1.5], and for dental check-ups (OR = 1.5). Receipt of restorative and expensive services (OR = 1.4) was more likely by those with both public and commercial insurance. Tooth extraction was more likely in subjects with no insurance coverage (OR = 1.6). Conclusion This study revealed a positive relationship between insurance coverage and demand for and utilization of dental services in a country with a developing health care system.